Survey of Economic Effects of Bank Dispute 1970. - Ireland ([S.l.] : Central Bank, 1971)
At a time when political leaders of the member nations are not acting to strengthen the multilateral trading system via the World Trade Organization, it is worthwhile to reflect on the WTO's contributions to global welfare since its inception more than 65 years ago. This volume assembles seminal empirical studies which estimate the past and prospective, national and global economic welfare impacts of GATT/WTO-induced multilateral trade liberalizations. It also touches on the effects of the Uruguay Round's TRIPS Agreement on intellectual property rights, and the benefits from WTO accessions and trade facilitation initiatives. In his authoritative introduction, Professor Anderson points to the numerous additional contributions of the WTO (and its predecessor, the GATT) which, though difficult to quantify, are nonetheless of great value and highlights those areas where further empirical research could shed more light on the net benefits of this important institution.
aia 25/03/2019
Loans
Keywords: Banks and Banking; Industrial relations; Economic History